Pricing Warrant Bonds with Credit Risk under a Jump Diffusion Process - Xiaonan Su; Wei Wang; Wensheng Wang (Discrete Dynamics in Nature and Society)
This article investigates the pricing of the warrant bonds with default risk under a jump diffusion process. We assume that the stock price follows a jump diffusion model while the interest rate and the default intensity have the feature of mean reversion. By the risk neutral pricing theorem, we obtain an explicit pricing formula of the warrant bond. Furthermore, numerical analysis is provided to illustrate the sensitivities of the proposed pricing model.